Pengaruh Model Pembelajaran Probing Promting Terhadap Hasil Belajar Siswa pada Materi Sel pada Makhluk Hidup di Kelas XI IPA SMA Negeri 8 Buru Kecamatan Waplau - Muhamad Sehol (LP. Ma'arif Janggan Magetan, 2022)
The purpose of this study is to find out whether there is an influence of the promting probing learning model on student learning outcomes on the cell material of living things Class XI SMA Negeri 8 Buru This research was carried out at SMA Negeri 8 Buru class XI for the 2020/2021 school year. The samples used in this study were class X1 IPA2 as an experimental class and a control class. The data analysis technique used is a normality test, and a hypothesis test using the